Evaluation of phosphoric rock and steel slags as raw materials for the development of iron phosphate cements for applications in building materials (2021)
ABSTRACT: Chemically bonded phosphate ceramics (CBPC) have high mechanical strength, some exceeding the mechanical strength of Portland cements, such as magnesium phosphate cements (MPC). However, obtaining these cements involves the treatment of metal oxides through thermal processes with high energy consumption. Likewise, the most used chemical precursors is the orthophosphoric acid, which increase the costs in the synthesis of these cements. One approach to address the present problem includes the use of unconventional raw materials, which can provide the required ions in the acid-base reactions of these types of cements. EAF and BOF steel slags contain significant amounts of divalent metal oxides like wüstite (FeO) and divalent-trivalent metal oxides like magnetite that can act as formers of iron phosphate compounds. Likewise, the phosphoric rock used to obtain phosphate compounds and which in some regions of the world is underutilized because it does not have the content of P2O5 for industrial use processes, is presented as an important option in the formation of these cements. For this reason, this work evaluates the behavior of steel slag (EAF - BOF) and phosphoric rock as potential raw materials to form CBPC for possible applications in construction materials. Initially, a literature review is carried out to elucidate the advantages and disadvantages of phosphate cements in comparison with existing technologies and the mechanical possibilities of these cements as materials for applications as construction materials. Slag was collected from different steelworks in Colombia following standard sampling practice. The different raw materials were characterized by granulometric analysis, SEM / EDS, FTIR, XRD and XRF. The cements obtained were analyzed by XRD, SEM-EDS, FTIR, XPS, ICP-OES, ICC, TGA and compressive strength tests, the chemical stability of these compounds was also investigated to establish their durability. Three different types of CBPC were synthesized from the type of anionic precursor used, as they are: i) by using aqueous solutions of orthophosphoric acid, ii) by using concentrated phosphoric rock leached with H2SO4 and iii) by using potassium dihydrogen phosphate (KDP) KH2PO4. From the aqueous solutions of otophosphoric acid, multiphase phosphate cement was obtained with a glassy structure for the iron phosphate phases and a crystalline structure for the calcium phosphate phases, compressive strengths of up to 20 MPa were recorded for the different compositions evaluated, with short setting times. The use of phosphoric rock showed the formation of Brushite type calcium phosphates, the mechanical strengths recorded are mainly attributed to the abundant amount of anhydrite and gypsum present in the binder. To induce a greater formation of iron phosphates, the reaction of EAF slag and KDP is promoted, thus allowing the description of the kinetic model in the formation of slag-based phosphate cement, amorphous products were observed in the form of metal phosphate hydrates and a fraction of calcium silicate hydrates, similar to those found in Portland cement, the phosphate matrix allows the effective immobilization of heavy metals in the slag, such as Cr and As, mechanical tests showed a compressive strength of 15-25 MPa. The oxides contained in the slags (EAF-BOF), especially CaO and FeO act as alkaline components in acid-base reaction systems for the synthesis of CBPC, the cements thus formed show moderate mechanical strength and facilitate possible applications as construction materials, the type of acid component used influences the developed microstructure, showing amorphous structures, with a prevalent formation of iron phosphates as the main phase of these cements, conditioning the mechanical strength and improving the durability of the cement. The variety of oxides contained in slags affects the cement formation rate, limiting the type and quantity of formed cementitious products. EAF slag-based phosphate cement is presented as a possible real field application in mortars or structural bricks, which describes a new way of recycling slag to obtain cement, while reducing the environmental impact of phosphate cement synthesis, because it eliminates the high energy consumption required for the calcination of alkaline compounds, allowing in turn its use without restrictions as a construction material.